Une insertion professionelle inégale: l'importance de l'origine sociale dans les transitions professionnelles des jeunes en Argentine - Pérez, Pablo Ernesto (2016)
Contemporary analysis of youth professional integration takes three factors into account: academic qualifications, previous work experience and gender. Such an approach conceals a more structural dimension, namely social background. This article is based on research into how social background shapes the career paths of young people in Argentina.The article adopts a longitudinal approach, studying the world of work both quantitatively - using transition matrices assembled with microdata from the Permanent Household Survey (EPH) - and career transitions, in order to analyze longer-term professional integration pathways. It provides a better understanding of the relationship between structural factors affecting emplyment opportunities for youth and the meanings and viewpoints into play by young people themselves